2016
DOI: 10.1155/2016/2547169
|View full text |Cite
|
Sign up to set email alerts
|

Report on the Medicinal Use of Eleven Lamiaceae Species in Lebanon and Rationalization of Their Antimicrobial Potential by Examination of the Chemical Composition and Antimicrobial Activity of Their Essential Oils

Abstract: Many Lamiaceae species are consumed in the Lebanese cuisine as food or condiment and are largely used in the traditional medicine of Lebanon to treat various diseases, including microbial infections. In this article we report the traditional medicinal uses of eleven Lamiaceae species: Coridothymus capitatus L., Lavandula stoechas L., Lavandula angustifolia Mill., Mentha spicata L. subsp. condensata, Origanum syriacum L., Rosmarinus officinalis, Salvia fruticosa Miller., Satureja cuneifolia Ten., Satureja thymb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
84
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 55 publications
(47 reference statements)
8
84
0
6
Order By: Relevance
“…For the S . fruticosa , this is in accordance with the few studies available (Khoury, Stien, Eparvier, Ouaini, & El Beyrouthy, ). However, this is not the case of other Salvia species such as S .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…For the S . fruticosa , this is in accordance with the few studies available (Khoury, Stien, Eparvier, Ouaini, & El Beyrouthy, ). However, this is not the case of other Salvia species such as S .…”
Section: Resultssupporting
confidence: 92%
“…The EO of R . officinalis was also not effective toward tested microorganisms, which is comparable to a similar which showed an inhibitory activity at higher concentrations than those used herein (Khoury et al, ).…”
Section: Resultssupporting
confidence: 60%
“…Origanum ehrenbergii (OE)—known as “Zaayter”—is an endemic plant to Lebanon belonging to Lamiaceae family and growing at an altitude of up to 2000 m . This plant is used in traditional medicine as remedy for many gastrointestinal disorders and microbial infections …”
Section: Methodsmentioning
confidence: 99%
“…In traditional Lebanese medicine, T. spicata is used to treat arteriosclerosis, blood toxicity, cough, hypoglycaemia, insomnia, ophthalmia, sterility, and toothache, and is often used as a cardiotonic and oxytocic agent. Satureja thymbra is used to treat blood toxicity, cough, nephropathy, and paralysis, and is an anti‐inflammatory, an antidiarrheal, a cardiotonic agent, and an antiseptic . The essential oils of S. thymbra demonstrate strong antiproliferative capacity against MCF‐7 cells, which could be attributed to carvacrol and thymol .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of S. thymbra , the MIC values ranged from 0.1 (for Bacillus subtilis , Enterococcus faecalis , and Escherichia coli ) to 0.4 mg mL –1 (for Candida albicans ). The essential oils of S. thymbra and T. spicata exhibited antimicrobial and antifungal properties against pathogenic microorganisms typical in food, plants, animals, and humans, according to Markovic et al The results of Khoury et al confirmed that S. thymbra and T. spicata , used in Lebanese ethnopharmacological practices, can be used as antimicrobial agents in alternative or complementary medicine. Gumus reported that the antifungal properties of T. spicata change upon exposure to gamma irradiation …”
Section: Introductionmentioning
confidence: 99%